Morphometric Analysis to Identify the Perilesional Tissue in Oral Epithelial Dysplasia: A Novel Objective Tool (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: morphometry; epithelial dysplasia; perilesional tissue; oral potentially malignant disorders (OPMDs)